2017
DOI: 10.1038/s41598-017-09523-4
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Tunable Metamaterials Based on Multimaterial Nanowires Incorporating Transparent Conductive Oxides

Abstract: We present novel design approaches for metasurfaces and metamaterials with electrical tunability offering real-time manipulation of light and serving as multifunctional devices in near-infrared frequency regime (at the specific wavelength of 1.55 μm). For this purpose, we integrate indium-tin-oxide (ITO) as a tunable electro-optical material into multimaterial nanowires with metal-oxide-semiconductor and metal-insulator-metal configurations. In particular, an active metasurface operating in the transmission mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 63 publications
0
34
0
Order By: Relevance
“…However, the change in the carrier concentration is limited to a thin accumulation layer for ITO and to a two-dimensional surface for graphene. Due to this fact, these materials have been incorporated in resonant geometries which can enhance the light-matter interaction in the active regions and enable tunable modulation of phase over a wide range in reflection [19,20,[24][25][26][27] or transmission [28] through spectral shift of the resonance. Despite the fruitful progress that has been made toward electrically tunable modulation of light wavefront, all the proposed designs thus far suffer from a limited efficiency as they cannot cover the entire 2π span for phase modulation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the change in the carrier concentration is limited to a thin accumulation layer for ITO and to a two-dimensional surface for graphene. Due to this fact, these materials have been incorporated in resonant geometries which can enhance the light-matter interaction in the active regions and enable tunable modulation of phase over a wide range in reflection [19,20,[24][25][26][27] or transmission [28] through spectral shift of the resonance. Despite the fruitful progress that has been made toward electrically tunable modulation of light wavefront, all the proposed designs thus far suffer from a limited efficiency as they cannot cover the entire 2π span for phase modulation.…”
Section: Introductionmentioning
confidence: 99%
“…In this manuscript, n‐type silicon with the doping concentration of 5 × 10 16 cm −3 is assumed. It has been observed that applying different voltages directly to silicon will negligibly modify its optical characteristics like dissipative loss and frequency dispersion of dielectric constant . As shown in Figure e, an electrical bias can be applied across the top Si‐made nanodisk and the bottom gold back mirror.…”
Section: Resultsmentioning
confidence: 99%
“…4. The procedure for obtaining scattered fields in an aperiodic array is similar with the governing matrix equation being replaced with (19) and the scattered field being given by (15). Further details regarding technical implementation and assembling of matrices are given in the Supplemental Material 54 .…”
Section: E Scope Of the Methodsmentioning
confidence: 99%
“…In conventional designs of metamaterials, the gradient characteristics are achieved through geometrical variation of building blocks which makes their operation static, tying them to a specific application after fabrication. More recently, several efforts have been put into post-fabrication control of the metamaterials by exploiting mechanical reconfiguration 8,9 , thermal phase transitions 10,11 and electro-optical materials [12][13][14][15][16][17] in geometrically fixed platforms. Such tunable designs render more flexibility in the operation allowing for multifunctionality and on-demand manipulation of light.…”
mentioning
confidence: 99%